The global division of labour as enduring archipelago: thinking through the spatiality of `globalisation in reverse' - Michiel van Meeteren; Jana Kleibert (Cambridge Journal of Regions, Economy and Society, 2022)
Contemporary globalisation faces several challenges, for instance related to climate change, technological disruption and shifting geopolitics, that have repercussions for the organisation of value chains and the global division of labour. Analysing the long-term geographies of globalisation we observe how successive reconfigurations of `new' and `newer' global divisions of labour share an archipelagic socio-spatial structure. The paper theorizes the articulations of this archipelago spatial figure as a combination of de/bordering, dis/connecting and dis/association. We apply this framework to provide a nuanced assessment of how global capitalism might restructure when some processes that defined globalisation during the last decades kick in reverse.
Keywords: F60; N20; P10; P16; 330; International division of labour; uneven development; de-globalisation; world-economy; archipelago economy; macroeconomic geography